2020
DOI: 10.1021/acs.cgd.0c01415
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laser Parameters and Experimental Conditions on Nonphotochemical Laser-Induced Nucleation of Glycine Polymorphs

Abstract: Nonphotochemical laser-induced nucleation (NPLIN) is a promising primary nucleation control method, yet its underlying mechanism remains elusive. To contribute to the discussion on whether the polarization of laser irradiation in NPLIN experiments influences the polymorphic outcome, we revisit NPLIN experiments with aqueous glycine solutions with supersaturations ranging between S = 1.5 and S = 1.7 irradiated by nanosecond pulses (∼7 ns) of near-infrared wavelength (1064 nm). Systematically altering laser ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 49 publications
3
31
0
Order By: Relevance
“…There are, however, reported cases, such as Alexander and Camp [6], showing that the induction time is not correlated to polarization geometry. In the case of glycine, Garetz et al [2,16] have shown that, for a range of supersaturation, the geometry of polarization induces different polymorphs, which was considered in this study as an argument in favor of the OKE model (although this experiment could not be reproduced) [17,19]. K 2 SO 4 exhibits two polymorphs-the β form (Pnam (62)) [29], which is stable up to 583 • C but transforms into the α form at a higher temperature (P6 3 /mmc) [30].…”
Section: Influence Of the Laser Polarizationmentioning
confidence: 78%
See 2 more Smart Citations
“…There are, however, reported cases, such as Alexander and Camp [6], showing that the induction time is not correlated to polarization geometry. In the case of glycine, Garetz et al [2,16] have shown that, for a range of supersaturation, the geometry of polarization induces different polymorphs, which was considered in this study as an argument in favor of the OKE model (although this experiment could not be reproduced) [17,19]. K 2 SO 4 exhibits two polymorphs-the β form (Pnam (62)) [29], which is stable up to 583 • C but transforms into the α form at a higher temperature (P6 3 /mmc) [30].…”
Section: Influence Of the Laser Polarizationmentioning
confidence: 78%
“…This is in line with the observation of Hua et al [35], who found that the number of crystal nucleated is proportional to the laser intensity. Yet, it should be underlined that Irimia et al [19] showed that the nucleation probability of glycine aqueous solutions actually decreases when more than 600 pulses are used due to the overall temperature increase (and associated supersaturation decrease) of the solution. For our study, the temperature increase was calculated for our experimental conditions (1 pulse at 85.6 mJ, β = 1.25) using the same theoretical model developed and experimentally validated by Irimia et al The calculated Cp value of 3.75 J g −1 K −1 led to an overall increase in temperature (in the area illuminated by the laser) of 2.4 × 10 −3 K/pulse, which was not sufficient to change the overall supersaturation of the solutions.…”
Section: Influence Of the Number Of Pulses And Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…Polarization switching for glycine occurs only within a narrow window of supersaturation and temperature, and it has been found that switching is difficult to reproduce. 27,30,33,38,39 Polarization effects have also been observed in NPLIN of ʟ-histidine, 26 carbamazepine 28 and sulfathiazole. 29 The mechanisms of NPLIN are not fully understood.…”
Section: Introductionmentioning
confidence: 94%
“…[10][11][12][13][14][15] Non-photochemical laser-induced nucleation (NPLIN) is a technique in which a new phase is formed by the exposure of a metastable system to pulses of laser light. The phenomenon was first observed in supersaturated solutions of urea, 16 and has since been observed in a diverse range of systems including solutions of simple salts; [17][18][19][20][21][22] proteins; 23,24 small molecules in various solvents; 13,[25][26][27][28][29][30][31][32][33] and one-component systems. 34,35 NPLIN typically utilises millijoule, unfocused, nanosecond laser pulses in the visible or near-IR region of the electromagnetic spectrum at a wavelength that is not absorbed by the sample.…”
Section: Introductionmentioning
confidence: 97%